WarnerMedia - Fitzgerald, Scott (SAGE Publications, Inc., 2020)
Based in the United States, WarnerMedia, formerly Time Warner, is one of the world’s leading transnational media corporations, with operations focused on television programming and networks, films, and video games. Through the production and distribution of such media content over multiple digital distribution platforms, the corporation remains central to the international development of video-based entertainment and news. In 2016, Time Warner generated more than $29 billion in revenues from its three operating divisions: Turner, Home Box Office, and Warner Bros. In the same year, the corporation announced it had entered into an $85 billion deal to be acquired by AT&T, the world’s largest telecommunications company, in a stock-andcash transaction.